2006
DOI: 10.1097/01.ana.0000206229.38883.d2
|View full text |Cite
|
Sign up to set email alerts
|

Bispectral Index and Spectral Entropy in Neuroanesthesia

Abstract: Spectral Entropy (SpEn) is an alternative tool to the bispectral index (BIS) for monitoring depth of hypnosis. SpEn measures response entropy (RE) and state entropy (SE). This open-label prospective study was designed to evaluate SpEn and BIS in 20 patients undergoing elective supratentorial neurosurgery with craniotomy and resection of brain tumors. SpEn and BIS were obtained continuously by Datex Ohmeda M-entropy module S/5 (Helsinki, Finland) and Aspect Medical System BIS (Newton), respectively. Total intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…However, our study revealed that the use of propofol alone at an effect site concentration between 2.0-5.1 µg/ml was not an influential factor on the RE and SE values (Table 5 and 6). A prior model did not exclude the effects of opioid, muscle relaxants and intraoperative stimulations on spectral entropy values at a propofol plasma concentration between 2.5 and 5 µg/ml, which was similar to the propofol concentration of our study [22]. Thus, we presume that a reason of why the result of our study was different from the one of previous study [22] is likely the presence or absence of the effects of perioperative medications on RE and SE.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…However, our study revealed that the use of propofol alone at an effect site concentration between 2.0-5.1 µg/ml was not an influential factor on the RE and SE values (Table 5 and 6). A prior model did not exclude the effects of opioid, muscle relaxants and intraoperative stimulations on spectral entropy values at a propofol plasma concentration between 2.5 and 5 µg/ml, which was similar to the propofol concentration of our study [22]. Thus, we presume that a reason of why the result of our study was different from the one of previous study [22] is likely the presence or absence of the effects of perioperative medications on RE and SE.…”
Section: Discussionmentioning
confidence: 63%
“…A prior model did not exclude the effects of opioid, muscle relaxants and intraoperative stimulations on spectral entropy values at a propofol plasma concentration between 2.5 and 5 µg/ml, which was similar to the propofol concentration of our study [22]. Thus, we presume that a reason of why the result of our study was different from the one of previous study [22] is likely the presence or absence of the effects of perioperative medications on RE and SE. Using propofol alone for anesthetic induction, based on the results of our study, we figured out that the spectral entropy values were not interfered by a propofol Ce between 2.0-5.1 µg/ml.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Clinicians can be frustrated by uneven performance or overly complicated algorithms and appear to be more accepting of a simple algorithm than a complicated one, and a widely accepted simple algorithm is shown in Figure 3 (Bell et al, 1991;Paolo Martorano et al, 2006). When an algorithm makes an inaccurate classification, the level of complexity of the algorithm seems to be proportional with the level of acceptance of that mistake.…”
Section: Pitfallsmentioning
confidence: 99%
“…1 In addition, entropy monitoring is useful to differentiate between inadequate analgesia from anesthesia. 1 In addition, entropy monitoring is useful to differentiate between inadequate analgesia from anesthesia.…”
Section: To the Editormentioning
confidence: 99%